2008
DOI: 10.1038/jhh.2008.21
|View full text |Cite
|
Sign up to set email alerts
|

The risk factors for elevated blood pressure and how to address cardiovascular risk factors: a review in paediatric populations

Abstract: This paper examines the epidemiology of hypertension and management strategies of cardiovascular diseases (CVDs) in paediatric populations in sub-Saharan Africa and other parts of the world in the 21st century. A computerized literature search was carried out using Medline, Evidence-Based Child Health (A Cochrane Review Journal), the Cochrane Library and Cochrane Child Health Field. A manual search in the African Journal for physical, health education, recreation and dance, the South African Journal for Resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…15 This gender difference may be attributed to hormonal changes that occur during puberty which had been noted to occur more rapidly in females than in males and also the stress associated with menarche could be one of the reason. 16 Significant association was found with the intake of junk food for the frequency of >=4 times a week in our study. Similarly Satyanarayanaetal found significant association with junk food intake among Hyderabad adolescents.…”
Section: Discussionsupporting
confidence: 53%
“…15 This gender difference may be attributed to hormonal changes that occur during puberty which had been noted to occur more rapidly in females than in males and also the stress associated with menarche could be one of the reason. 16 Significant association was found with the intake of junk food for the frequency of >=4 times a week in our study. Similarly Satyanarayanaetal found significant association with junk food intake among Hyderabad adolescents.…”
Section: Discussionsupporting
confidence: 53%
“…The results were similar to a previous study by Must et al [36], who reported that underweight was significantly associated with poor strength among Indian youth. Physiologically, this could be due to poor dietary or energy intake that leads to underweight and poor strength [5,37]. Furthermore, thinner people often have poor strength, higher illness prevalence, and greater mortality than those with…”
Section: Discussionmentioning
confidence: 99%
“…It increases the risk of cardiovascular diseases among children and adults in the developed and developing countries [2][3][4][5]. body mass index (bMI) has been used widely as an indicator for malnutrition, although it has been recently argued that bMI reflects also the relative leg length, body frame size, and fat free mass in addition to fatness [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The BP and anthropometric measurements were taken directly; hence, recall or estimation bias will not prevail in our study. In addition, we measured BP during early childhood, signifying that early monitoring should commence from children's early days in order to identify and screen individuals that show vulnerability to associated risk factors [24].…”
Section: Discussionmentioning
confidence: 99%